Improving marketing and traceability of agricultural commodities: The role of cooperatives - llebani, Olabisi A. (International Food Policy Research Institute, 2010)
Farmer cooperatives are viewed as mechanisms to help improve the marketing environment for poor rural farmers faced with limited and uncertain consumer demand for the goods they produce. Cooperatives can help reduce production costs by organizing bulk input purchases for their members. They may also be used as social organizations and serve as a medium for enlightenment and capacity building. This brief explores the role of farmers' cooperatives in Nigeria by assessing their effectiveness in marketing and traceability services, as well as elucidating the constraints they face.